0622 In-Depth Surveillance of Central Sleep Apnea in Patients with Stable Heart Failure. (27th May 2020) - Ibrahim, S; Wharton, R; Harmon, E; Bonner, H; Davis, E; Cho, Y; Mazimba, S; Kwon, Y
Abstract: Introduction: Central sleep apnea (CSA) is unique sleep breathing phenotype in patients with advanced chronic heart failure (HF) and portend poor prognosis. The prevalence of CSA in HF patients under contemporary therapy is uncertain. Methods: We reviewed consecutive HF patients on optimal medical therapy who underwent clinically indicated diagnostic in-lab polysomnography at a single academic center. Age, sex and BMI matched patients without HF were selected from sleep clinic as a control. Patients with atrial fibrillation were excluded from this study. Apnea subtypes were determined after careful scoring and confirmation by sleep physicians. 'Any CSA' was defined by central apnea index (CAI) >5 and >1/hr. 'True CSA' was defined if met both CAI≥5/hr and > obstructive apnea index (OAI). Obstructive sleep apnea (OSA) was defined if apnea hypopnea index >15 and OAI>CAI. Multivariate analysis was performed using logistic regression adjusting for age, sex, HF and systolic dysfunction as appropriate. Results: In patients with HF (N=95, mean age 59, female: 50%), CSA was low and was comparable to control group (N=94) (HF vs. Non-HF; CSA: 5.3 vs. 4.3%, P=NS; Any CSA 14.7 vs. 17%, P=NS). Only 3 patients with HF had true CSA. In contrast, OSA was common in both groups regardless of obesity status (52.3 vs. 55.3%). In patients with HF, Cheyne Stokes respiration was more frequent in patients with Any CSA vs. without Any CSA (13.3 vs. 3.8%, p=0.04). In multivariate analysis, presence of OSA, but not HF, was associated with Any CSA in entire cohort (Any CSA OR: 3.1 [1.3, 8.1], p=0.02). In patients with HF, male sex was associated with Any CSA (OR: 5.3 [1.1, 40.8], p=0.05). Exclusion of patients with high BMI did not change the results. Conclusion: CSA was rare in patients with stable HF on contemporary optimal medical therapy. Support: None